Implementasi Akad Salam dalam Sistem Penjualan Online di Kwala Official - Ivana Kalista Intan Pratama; Naurah Syahla, Farelia; Lestari, Amanda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of the Salam contract in the online sales system of Kwala Official, an online store selling bedding through the marketplaces Shopee, Tokopedia, TikTok, and Blibli. The research method used a qualitative case study approach, with data collection techniques through interviews, observation, and documentation. The results indicate that online sales transactions at Kwala Official reflect the principles of the Salam contract, characterized by advance payment before receiving the goods, clear product information, and guaranteed delivery times. Furthermore, the implementation of the Salam contract is further strengthened by the marketplace system, which provides advance payment facilities, return policies, and refund mechanisms, thus providing protection for buyers. The study also identified supporting factors, such as clear product descriptions and good store management, as well as inhibiting factors such as shipping delays caused by the shipping company, differences in product appearance, and marketplace technical issues. Overall, transaction practices at Kwala Official comply with the terms and conditions of the Salam contract from a Sharia perspective.